A new genetic model for calcium induced autophagy and ER-stress in Drosophila photoreceptor cells - Weiss, Shirley (Channels (Austin), 2015)
Cytoplasmic Ca(2+) overload is known to trigger autophagy and ER-stress. Furthermore, ER-stress and autophagy are commonly associated with degenerative pathologies, but their role in disease progression is still a matter of debate, in part, owing to limitations of existing animal model systems. The Drosophila eye is a widely used model system for studying neurodegenerative pathologies. Recently, we characterized the Drosophila protein, Calphotin, as a cytosolic immobile Ca(2+) buffer, which participates in Ca(2+) homeostasis in Drosophila photoreceptor cells. Exposure of calphotin hypomorph flies to continuous illumination, which induces Ca(2+) influx into photoreceptor cells, resulted in severe Ca(2+)-dependent degeneration. Here we show that this degeneration is autophagy and ER-stress related. Our studies thus provide a new model in which genetic manipulations trigger changes in cellular Ca(2+) distribution. This model constitutes a framework for further investigations into the link between cytosolic Ca(2+), ER-stress and autophagy in human disorders and diseases.